2014
DOI: 10.4236/ojpm.2014.47063
|View full text |Cite
|
Sign up to set email alerts
|

Prelacteal Feeding Practice and Associated Factors among Mothers Attending Immunization Clinic in Harari Region Public Health Facilities, Eastern Ethiopia

Abstract: Background: Breast feeding will have the intended outcome when it is initiated timely and exclusive for the first six months. Introducing prelacteal feeding and inadequate amount of breast milk contributes to over a million avoidable infant deaths each year in developing countries. The purpose of this study was to assess prelacteal feeding practice and associated factors among mothers attending immunization clinic in Harari region government health institutions. Methods: An institutional based cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
76
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 7 publications
17
76
5
1
Order By: Relevance
“…5,6 The questionnaire was first prepared in English. Later, it was translated in to the local language Amharic and then back again to English.…”
Section: Instruments and Personnelmentioning
confidence: 99%
See 4 more Smart Citations
“…5,6 The questionnaire was first prepared in English. Later, it was translated in to the local language Amharic and then back again to English.…”
Section: Instruments and Personnelmentioning
confidence: 99%
“…For example, it was found that approximately 38.8% of women in Raya Kobo district and 45.4% of mothers in Harar gave prelacteal liquids to their infants. 5,6 The most common prelacteal foodstuffs are milk other than breast milk, plain water, sugar or glucose water, fresh butter, Ersho, salt water solution, fruit juice, infant formula, tea, and honey. 5,6 The most common reasons stated for PLF are insufficient milk production, advice from elders, family custom, assumption that it is good for health (child will talk early and tongue will become thin), to remove meconium from the gut of the child, and to prevent "evil eye" and illness.…”
mentioning
confidence: 99%
See 3 more Smart Citations